2008
DOI: 10.1002/app.27629
|View full text |Cite
|
Sign up to set email alerts
|

Study of the behavior of polyester concretes containing ionomers as curing agents

Abstract: Polyester concretes have been used in constructions for more than 20 years. This type of polymer concrete can advantageously replace traditional Portland concrete in situations that require fast consolidation of the material. Otherwise, polyester concretes are usually more expensive than Portland concretes. Part of the high cost of the polyester concretes is due to the fact that the aggregates used in the formulation of the concretes need to be dried prior to their incorporation into the polymer matrix. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…They found that such an ionomeric UPR showed improved mechanical properties (according to the ABNT NBR 5759 standard) in both the dry and the wet states. As a possible explanation for this behavior, the authors reason that water molecules would be trapped inside the ionic cages formed by the charged groups and, hence, would be less available to interfere with the curing process [174].…”
Section: Polymer Concretesmentioning
confidence: 98%
See 2 more Smart Citations
“…They found that such an ionomeric UPR showed improved mechanical properties (according to the ABNT NBR 5759 standard) in both the dry and the wet states. As a possible explanation for this behavior, the authors reason that water molecules would be trapped inside the ionic cages formed by the charged groups and, hence, would be less available to interfere with the curing process [174].…”
Section: Polymer Concretesmentioning
confidence: 98%
“…As drying comprises an additional energyintensive production step, this adds to the high cost of polymer concrete and may be a critical quality factor in the production process. To circumvent this, Ignacio and co-workers [174] made use of the ionic functionalities introduced into the polymeric matrix when methacrylic acid and maleic anhydride were used for curing of an isophthalic acid-based UPR. They found that such an ionomeric UPR showed improved mechanical properties (according to the ABNT NBR 5759 standard) in both the dry and the wet states.…”
Section: Polymer Concretesmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles, that were previously crushed and classified, were dried, weighed and putted in a vacuum planetary mixer. Dry particles are a necessary step because water may reduce the cure process efficiency related to adhesion between the composite components 10 . The unsaturated polyester was introduced into the mixer by vacuum suction.…”
Section: Fabrication Of Slabs From Residuementioning
confidence: 99%
“…UPE curing is an exothermic reaction accompanied with viscosity growth due to molecular weight increase to form a threedimensional cross-linked network [7][8][9][10][11]. The mechanical properties of the resin and its adhesion to aggregates in PC are the main sources of the advantageous mechanical properties of PC for its application in precision tool machine bases [12,13], where PCs (polymer concretes) are used due to their high damping properties and their ability to absorb unwanted system vibrations [14].…”
Section: Introductionmentioning
confidence: 99%